2003
DOI: 10.1029/2002pa000829
|View full text |Cite
|
Sign up to set email alerts
|

Pliocene summer sea surface temperature reconstruction using silicoflagellates from Southern Ocean ODP Site 1165

Abstract: In the modern marine environment the silicoflagellate genus Dictyocha is rare, or absent, south of the Antarctic polar front (APF); the genus Distephanus, in contrast, is dominant. In sediments recovered from ODP Site 1165, 1600 km south of the front, however, three intervals where Dictyocha is abundant are interpreted to represent Pliocene warm events. Comparison of our data with Ciesielski and Weaver's [1974] modern core top silicoflagellate relationship with sea surface temperature (SST) indicates that at S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 69 publications
(136 reference statements)
8
63
2
Order By: Relevance
“…Warm Pliocene seasonal temperatures up to 6°C warmer than today during interglacials and prolonged Pliocene warm intervals have been reported in the Ross Sea 535 (e.g., Naish et al, 2009;McKay et al, 2012) and other locations around Antarctica (Whitehead and Bohaty, 2003;Whitehead et al, 2005;Escutia et al, 2009;Bart and Iwai, 2012). Contrary to what we observe in our late Oligocene record, during the warm Pliocene abundant IRD were delivered to adjacent continental rise sites (Escutia et al, 2011;Patterson et al, 2014).…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…Warm Pliocene seasonal temperatures up to 6°C warmer than today during interglacials and prolonged Pliocene warm intervals have been reported in the Ross Sea 535 (e.g., Naish et al, 2009;McKay et al, 2012) and other locations around Antarctica (Whitehead and Bohaty, 2003;Whitehead et al, 2005;Escutia et al, 2009;Bart and Iwai, 2012). Contrary to what we observe in our late Oligocene record, during the warm Pliocene abundant IRD were delivered to adjacent continental rise sites (Escutia et al, 2011;Patterson et al, 2014).…”
contrasting
confidence: 58%
“…For example, the early Pliocene (5-3 Ma) has been targeted because atmospheric CO 2 concentrations were similar to today's (400 ppmv) concentrations (Foster and Rohling, 2013;Zhang et 80 al., 2013). These studies have shown that early Pliocene Southern Ocean surface waters were much warmer (i.e., between 2.5-> 4 ºC) than present and that the summer sea ice cover was greatly reduced, or even absent (Bohaty and Hardwood, 1998;Whitehead and Bohaty, 2003;Escutia et al, 2009;Cook et al, 2013). They also record the periodic collapse of both the WAIS and EAIS marine-based margins (Naish et al, 2009;Pollard and DeConto, 2009;Cook et al, 2013;Reinardy et al, 2015;DeConto and 85 Pollard, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, micropalaeontological data from ODP Leg 188 Site 1165 in the Indian Sector of the Southern Ocean indicate that during the early and middle Pliocene surface water temperatures south of the APF were, episodically, up to ca. 5°C higher than today (Whitehead and Bohaty, 2003), and sea-ice coverage was significantly reduced between ca. 5 Ma and 2.3 Ma (Whitehead et al, 2005) (Fig.…”
Section: The Late Pliocene Cooling Stepmentioning
confidence: 94%
“…stable oxygen isotope measurements from A. anderssoni in Williams et al 2010) or indirectly using species tolerances (e.g. the ratio of Dictyocha/Distephanus used by Whitehead and Bohaty 2003), that there was a reduction in sea ice during these warmer intervals. These data have been sourced from various environments both on land (deposits discussed in this paper), in shallow marine deposits, and beneath the ocean from core material.…”
Section: Sea Surface Temperaturesmentioning
confidence: 99%
“…A number of proxies have converging temperature data; for example maximum temperatures of up to +5°C during the summer months have been calculated in deposits of overlapping ages (4.6 to 3.3 Ma) in Prydz Bay, the Vestfold Hills, Ross Sea and the western Antarctic Peninsula margin using silicoflagellates (Whitehead and Bohaty 2003;Escutia et al 2009), diatoms (Whitehead et al 2001;Scherer et al 2010), and vertebrates (Quilty et al 1990;Quilty 1991;Quilty 1993); see Table 4 for details. These same data also indicated a reduction in sea ice and open ocean conditions during the summer months.…”
Section: Sea Surface Temperaturesmentioning
confidence: 99%